Integrated High‐Entropy Alloy Nanowire/Carbon Nanotube Membrane Electrode for Efficient Hydrogen Evolution in Acid Solution - Yang, Hao; Zhang, Zichu; Wang, Zhaoming; Zhang, Feng; Liu, Shaokang; Zhang, Lili; Shi, Chao; Hou, Peng‐Xiang; Cheng, Hui‐Ming; Wang, Xiao; Liu, Chang (Advanced functional materials, 2025)
Proton exchange membrane water electrolysis is one of the most promising techniques for industrial green hydrogen production. However, the electrocatalysts for hydrogen production have suffered from low activity and poor durability in acidic environment. Here an integrated membrane electrode composed of N‐doped carbon‐coated high‐entropy nanowires (HEA NWs) anchored on a single‐walled carbon nanotube (SWCNT) network is reported for efficient and stable hydrogen evolution reaction (HER). The residue surfactant remaining on the HEA NWs prepared by a wet chemistry method is transformed to a N‐doped carbon layer when fast heating the HEA NWs loaded on a SWCNT film, which firmly connects the ultrathin HEA NWs with SWCNT bundles. When used as an integrated membrane electrode, the hybrid film showed not only a low overpotential of 42 mV at 100 mA cm−2 for HER but also excellent durability up to 1000 h at 500 mA cm−2 in acid solution. The desirable performance is attributed to the hierarchical structure of the membrane electrode, where 1D HEA NWs anchored on SWCNT network function in regulating the hydrogen adsorption of H*, facilitating electron transfer, and protecting the nanowires from degradation. An integrated membrane electrode composed of N‐doped carbon‐coated high‐entropy alloy nanowires on SWCNT networks is reported. The hybrid film achieves 42 mV@100 mA cm⁻2 and 1000 h stability@500 mA cm⁻2 in HER, owing to optimized hydrogen adsorption, enhanced electron transport, and robust nanowire‐carbon nanotube connections. This design shed light on overcoming challenges of activity and stability of acidic HER electrocatalysts.